Factors influencing health-promoting lifestyles in patients after percutaneous coronary intervention: A cross-sectional study - Zhijie Cao; Ping Yan; Jing Ma; Lina Ma; Xin Gu; Hu Peng; Li Zhang (Scientific Reports)
Abstract Coronary atherosclerotic heart disease is one of the most common diseases, and health-promoting behaviors such as diet, exercise, and lifestyle habits are essential to improve the prognosis of patients with coronary heart disease. This study aimed to assess the health-promoting lifestyle status of patients following percutaneous coronary intervention and to analyse its influencing factors. A survey was conducted among 300 patients who had undergone percutaneous coronary intervention. Data were collected using a general information questionnaire and the Health-Promoting Lifestyle Profile. Multiple linear regression analysis identified ethnicity, monthly household income, and the presence of comorbidities as significant factors influencing the health-promoting lifestyle of these patients. The average scores for the health-promoting lifestyle post-intervention were (162.91 ± 12.24), which are considered favourable. The components of the health-promoting lifestyle were ranked from highest to lowest based on subscale scores: self-actualisation, interpersonal support, stress management, nutrition, health responsibility, and exercise. Healthcare professionals should tailor health education programs for patients based on their ethnic backgrounds, income levels, and whether they have comorbid conditions. This targeted approach can effectively enhance their health responsibility and improve their overall health-promoting lifestyle.